(untitled) (Proceedings of International Educators Conference, 2023)
In this article is devoted to one of the actual problems of chemistry subject - the use of chemical experiments in chemistry teaching. The «chemical experiment» is considered as a teaching method. The use of chemical experiment in teaching process helps to students in understanding the diversity of studied chemical acts, their nature, the real essence and dependence on test conditions.